Islam dan Revolusi: Posisi dan Peran Ulama dalam Revolusi Islam Iran - Fahruddin Fahruddin (el Harakah: Jurnal Budaya Islam, 2007)
This article explains that Islam, as a religion, demonstrates phenomena of social revolution. One of essential revolutions is Iranian Revolution. It has attracted almost all elements of society, from grass roots to elites. The discussion of Iranian Revolution is always interconnected with Moslem intellectuals. They were the decision makers of the revolution. There was the viewpoint discrepancy of Moslem intellectuals before and after the revolution. Before Iranian revolution, they had similar idea to end the authoritarian rezime (Reza Pahlevi) which was supported by the Western countries. However, after the revolution, Muslim intellectuals grew to be two groups: the reformism and the conservatism. Both groups see the authority of wilayah al faqih differently. The reformist group thought that wilayah al faqih was not valid to be the guide after revolution, but conservative group viewed conversely. Artikel ini menjelaskan bahwa sebagai agama, Islam menunjukkan fenomena revolusi sosial. Salah satu revolusi yang penting ialah revolusi Iran. Ia menarik perhatian hampir seluruh elemen masyarakat dari kaum pribumi hingga kaum elit. Diskusi tentang Revolusi Iran selalu berhubungan dengan cendekiawan Muslim. Mereka adalah pembuat keputusan dalam revolusi. Ada ketidakcocokan sudut pandang cendekiawan Muslim sebelum dan sesudah revolusi. Sebelum revolusi Iran, mereka sependapat untuk mengakhiri rezim otoriter (Reza Pahlevi), yang didukung oleh negara-negara Barat. Sebaliknya, setelah revolusi, cendekiawan Muslim terbagi dua golongan: reformis dan konservatif. Kedua grup memandang otoritas wilayah al faqih secara berbeda. Grup reformis berpendapat bahwa wilayah al faqih tidak valid untuk dijadikan pedoman setelah revolusi, sedangkan grup konservatif berpendapat sebaliknya.